Flexibility approach in construction process engineering - Paslawski, Jerzy (Technological and Economic Development of Economy, 2008)
The issues of environmental impact on building processes constitute a permanent aspect of the building industry, irrespective of various preventive actions (prefabrication, robotics etc.). The proposed method was developed in the course of tracking problems that arise during performance of building processes exposed to weather impact (as an example of interruptions) on construction sites of airports, highways, logistic centres, or installation of tall building facades. The proposed approach is based on creating multiple variants for process realization options, thus enabling adaptation to current realization conditions at particular stages. The studies that have been carried out confirm the advantage of this method over the traditional planning based on a single realization variant.Lankstumas statybos proceso inžinerijojeSantrauka. Aplinkos poveikis statybos procesui yra būdingas statybos pramonei nepaisant prevencinių veiksmų (surenkamųjų elementų gamyba, robotizacija). Pasiūlytas metodas buvo sukurtas stebint problemas, atsirandančias vykdant oro sąlygų veikiamus statybos procesus (pavyzdžiui, trikdžius) oro uostų, magistralinių kelių, logistikos centrų, aukštų pastatų fasado įrengimo darbų, statybos aikštelėse. Sukurtojo metodo esmė – pasiūlyti daug variantų konkrečiam procesui įvykdyti. Tai leidžia parinkti tam tikras konkrečių darbų etapų įvykdymo sąlygas. Tyrimas patvirtino, kad šis metodas pranašesnis už tradicinį planavimą, teturintį vienintelį darbų įvykdymo variantą.Reikšminiai žodžiai: lankstumo valdymas, statybos inžinerija, statybos procesas, planavimas irstebėsena.First published online: 21 Oct 2010